Sodium glucose cotransporter 2 inhibitor dapagliflozin depressed adiposity and ameliorated hepatic steatosis in high-fat diet induced obese mice. (1st January 2021) - Han, Tuo; Fan, Yajie; Gao, Jie; Fatima, Mahreen; Zhang, Yali; Ding, Yiming; Bai, Liang; Wang, Congxia
ABSTRACT: With the increasing obesity prevalence, the rates of obesity-related diseases, including type 2 diabetes, non-alcoholic fatty liver disease (NAFLD), and cardiovascular diseases, have increased dramatically. Dapagliflozin, one of the sodium glucose cotransporter inhibitors, not only exerts hypoglycaemic effects through increasing urinary glucose excretion but alsoreprograms the metabolic system, leading to benefits in metabolic and cardiovascular diseases. In this study, pre-established obese mice on a high-fat diet were given dapagliflozin by gavage for fourweeks. It showed that dapagliflozin can enhance fat utilization and browning of adipose tissue and improve local oxidative stress, thus inhibiting fat accumulation and hepatic steatosis without disturbance in body weight or plasma glycolipid level. Overall, our study highlights the potential clinical application of SGLT2 inhibition in the prevention of obesity and related metabolic diseases, such as insulin resistance, NAFLD, and diabetes.